2022
DOI: 10.3390/ijerph19159114
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Experience of Stress: A Focus Group Interview Study with 16–19-Year-Old Students during the COVID-19 Pandemic

Abstract: The purpose was to investigate stress among adolescents (16–19 years old) during the coronavirus disease 2019 (COVID-19) pandemic. Focus group (n = 9) interviews with students at upper secondary schools (16–19 years old, n = 41) were conducted in southern Sweden during the COVID-19 pandemic in 2021. The interviews were analyzed by qualitative content analysis. The analysis revealed five categories of experience of stress: (1) School-related stress, (2) Stress in relationships and leisure, (3) How stress manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Fifty unique publications were subjected to quality assessment using the MMAT tool [ 39 , 40 , 44 54 , 56 , 59 , 61 , 62 , 64 73 , 75 79 , 82 , 83 , 85 87 , 89 , 90 , 92 94 , 97 , 99 102 , 104 , 109 , 110 ] ( S2 Table ). Forty-three studies met 100% of MMAT criteria; [ 39 , 40 , 44 , 48 54 , 56 , 59 , 62 , 64 70 , 72 , 73 , 75 79 , 82 , 83 , 85 , 87 , 89 , 90 , 92 94 , 97 , 99 102 , 109 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Fifty unique publications were subjected to quality assessment using the MMAT tool [ 39 , 40 , 44 54 , 56 , 59 , 61 , 62 , 64 73 , 75 79 , 82 , 83 , 85 87 , 89 , 90 , 92 94 , 97 , 99 102 , 104 , 109 , 110 ] ( S2 Table ). Forty-three studies met 100% of MMAT criteria; [ 39 , 40 , 44 , 48 54 , 56 , 59 , 62 , 64 70 , 72 , 73 , 75 79 , 82 , 83 , 85 , 87 , 89 , 90 , 92 94 , 97 , 99 102 , 109 , ...…”
Section: Resultsmentioning
confidence: 99%
“…There is a positive role of social support on quality of life and mental health, facilitating the persons to sense appreciation and connection with various networks of society. Such feeling will impact mental health, reduce mental illness, and prevent depression symptoms (Perming et al, 2022;Ragab et al, 2021). In our results, it was observed that family and friends social support are predictors of symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%